ACADEMIC CAREER INTERESTS IN ACCOUNTING AND DARK TRIAD: EVIDENCE OF THE BRAZILIAN STUDENTS - Frigo Souza, Fabiana; França Lopes, Iago; Costa, Flaviano; Colauto, Romualdo Douglas (Advances in Scientific and Applied Accounting, 2021)
Objective: The study aimed at verifying the association between Dark Triad and the interest in activities related to academic career among postgraduate accounting students. Method: The sample consisted of 124 students from postgraduate programs in the Accounting Sciences in Brazil. Data were collected through a survey and submitted to multivariate analysis. Results: The results show that narcissism and psychopathy are related to activities inherent to the academic career, while Machiavellian traits do not exhibit the same association. The lack of correlation between Machiavellianism and academic career activities may be related to the desired academic career profile. Students with narcissistic traits are adept at academic career activities mainly related to research and teaching. Psychopathic traits were not adept at activities related to teaching and extension (service to the external community), which may be related to the lack of empathy, lack of concern related to compliance with rules and insensitivity. Contributions: The study contributes to the gap in accounting research that discusses non-pathological personality traits and career interests, since previous research has demanded attention in view of the objective and subjective issues inherent to the career and, at times, marginalize the relevant activities career choice. In addition, such discussions are presented as an advisory material for HEIs in terms of outlining the performance and interest of future teachers regarding the activities inherent to the academic career.